2016
DOI: 10.1186/s13027-016-0073-x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B and C viruses and risk of non-Hodgkin lymphoma: a case-control study in Italy

Abstract: BackgroundHepatitis C virus (HCV) has been consistently associated to non-Hodgkin lymphoma (NHL); conversely, few studies have evaluated a comprehensive serological panel of hepatitis B virus (HBV) in NHL etiology.MethodsWe conducted a case-control study in Italy in 1999–2014, enrolling 571 incident, histologically confirmed NHLs and 1004 cancer-free matched controls. Study subjects provided serum for HCV and HBV testing and for HCV RNA. Odds ratios (ORs) and corresponding 95 % confidence intervals (CIs) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 28 publications
(36 reference statements)
1
39
0
1
Order By: Relevance
“…The literature search flow diagram is shown in Figure . According to the preset criteria for inclusion and exclusion, 9 cohort studies containing 1585 NHL incident cases among a total cohort size of 2 708 191 subjects and 49 case–control studies containing 52 129 NHL cases and 1 778 591 controls were finally enrolled in this analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search flow diagram is shown in Figure . According to the preset criteria for inclusion and exclusion, 9 cohort studies containing 1585 NHL incident cases among a total cohort size of 2 708 191 subjects and 49 case–control studies containing 52 129 NHL cases and 1 778 591 controls were finally enrolled in this analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Although a positive association between HBV and NHL was found in 1994, it has been less studied compared with HCV. Nevertheless, a few case–control studies have demonstrated the increasing prevalence of HBV infection (2.21‐3.67 fold) in patients with NHL in Korea, China, and Italy . However, a population‐based nested case–control study that used the Surveillance, Epidemiology, and End Results‐Medicare data in the United States and recent studies by the European Prospective Investigation into Cancer and Nutrition study, and the Epilymph consortium found no significant association between chronic hepatitis B infection and NHL.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the 70s’, the prevalence of HBsAg chronic carriers in the general population was estimated over 3% with an increasing gradient from northern to southern Italy where this rate was close to 5%, and the proportion of HBeAg‐positive cases among HBsAg chronic carriers reached 40% . HBV genotype D was responsible for nearly 90% of cases with chronic HBV infection, independently from the disease progression; however, only few studies investigated on the viral strains circulating in recent years .…”
Section: Hbv Epidemiology In Italymentioning
confidence: 99%
“…Taborelli et al described the potential association between chronic HBV infection and non‐Hodgkin lymphoma in a case‐control study performed in Italy from 1999 to 2014; 571 incident cases of histological confirmed NHLs and 1004 of cancer‐free matched controls had been enrolled. The prevalence of HBsAg seropositivity was 3.7% in NHL cases and 1.7 % in controls, leading to an OR of 1.95 (95%CI:1.00‐3.81).…”
Section: Hbv Epidemiology In Italymentioning
confidence: 99%